A POST-COLONIAL PERSPECTIVE ON AFRICAN EDUCATION SYSTEMS - Getahun, Abraham (African Journal of Education and Practice, 2020)
Purpose: The purpose of this article is to discuss about precolonial and colonial education and the development of the education systems in the postcolonial Africa. The paper will deal with the questions whether there were any education systems in precolonial Africa and motives for introducing the colonial education systems. Further the relation of the colonial education systems with the needs of the local society, the postcolonial education systems and their future will be analysed. Methodology: Postcolonial perspective is a theoretical frame for the study. A desk-research was conducted to identify and select the relevant literature. Content analysis was used as a method to understand, analyse and interpret the literature. Findings: The results of the literature review show that there were socialization mechanisms before colonialism in African societies. Education introduced in its modern form by missionaries was supposed to serve mainly religious purposes and to train low level functionaries by colonial states. Instead of focusing on local realities education was used to teach the glories of the colonial countries, spread their language and culture as well as introduce a new way of life by condemning all that was native. After independence the inherited colonial education systems continued isolating the masses who had no access to the colonial languages. Unique contribution to theory, practice and policy: Findings of this study shows some limitations in African education systems. It is necessary that education policy makers and other concerned stakeholders´ to increase the use of local languages to reach the society at large, to focus on contents relevant to their contexts, to provide both theoretical and skill-based education useful for development of society and to aim towards educating productive, conscious, critical and democratic citizens.